2012
DOI: 10.1007/s00442-012-2306-z
|View full text |Cite
|
Sign up to set email alerts
|

Coral recovery may not herald the return of fishes on damaged coral reefs

Abstract: The dynamic nature of coral reefs offers a rare opportunity to examine the response of ecosystems to disruption due to climate change. In 1998, the Great Barrier Reef experienced widespread coral bleaching and mortality. As a result, cryptobenthic fish assemblages underwent a dramatic phase-shift. Thirteen years, and up to 96 fish generations later, the cryptobenthic fish assemblage has not returned to its pre-bleach configuration. This is despite coral abundances returning to, or exceeding, pre-bleach values.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 42 publications
1
56
0
Order By: Relevance
“…A study on the Great Barrier Reef found that fish communities have not returned to a pre‐bleaching composition more than 16 years after the 1998 bleaching event (Bellwood et al . ). Thus, it is perhaps not surprising that while some Seychelles reefs were showing signs of coral recovery 11 years after the 1998 bleaching event (Wilson et al .…”
Section: Discussionmentioning
confidence: 97%
“…A study on the Great Barrier Reef found that fish communities have not returned to a pre‐bleaching composition more than 16 years after the 1998 bleaching event (Bellwood et al . ). Thus, it is perhaps not surprising that while some Seychelles reefs were showing signs of coral recovery 11 years after the 1998 bleaching event (Wilson et al .…”
Section: Discussionmentioning
confidence: 97%
“…Studies have repeatedly shown, for both fishes and corals, that it is important to look beyond species richness if we wish to protect the world's reefs Bellwood, Hoey & Hughes, 2012b;Mouillot et al, 2013Mouillot et al, , 2014D'agata et al, 2014;Hughes et al, 2014). Thus while speciation and biodiversity may be interesting, they offer a dangerous distraction as reefs can rapidly lose critical functions while the biodiversity (species richness) remains relatively intact (Bellwood et al, , 2012aDornelas et al, 2014;Hughes et al, 2014).…”
Section: (B) the Functional Importance Of Species In Reef Ecosystems:mentioning
confidence: 94%
“…While these calculations may be affected by pulses in recruitment, e.g. [42,56] and density-dependent mortality effects [45,57], small fish communities are often remarkably stable [58][59][60][61] with the dominant species on coral reefs (e.g. gobies, acanthurids, chaetodontids [27,42]) often displaying continual recruitment [56].…”
Section: Discussionmentioning
confidence: 99%